Hermit Aesthetics in Chinese Metal Music: Subcultural Philosophy between Confucianism and Daoism - Zhao, Yiren (Scenari, 2024)
This article explores the “hermit aesthetics” within Chinese music subculture, drawing on the philosophies of Confucianism and Daoism. Using the Chinese metal band Zuriaake as a case study, it examines how the band constructs its aesthetic framework around the notion of the hermit and employs it to articulate the subcultural articulation within the Chinese context. Through discourse analysis of Zuriaake’s music, lyrics, and imagery, the article argues that, in addition to directly integrating the hermit image with metal traditions, the band employs two philosophical strategies: “withdrawing from the world”, rooted in Daoism, and “entering the world”, based on Confucianism. This reveals how Chinese metal artists navigate their subcultural position by maintaining a balance between self, morality, and politics, akin to the hermits depicted in their music.